Synthesis of Mg-doped TiO2 Using a Hydrothermal Method as Photoanode on Bixin-Sensitized Solar Cell - Winda Rahmalia; Intan Syahbanu; Nurlina; Ayu Widya Sari; Septiani (Universitas Andalas, 2023)
Titanium dioxide (TiO2) with magnesium (Mg) doping for dye-sensitized solar cell (DSSC) photoanode application has been synthesized. DSSC components used in this study were photosensitizer (bixin), electrolyte (), cathode (platinum), and photoanode (Mg-TiO2). This research aims to determine the characteristics of Mg-doped TiO2 photoanode with variations in dopant concentration based on the results of XRD and DR/UV-Vis analysis, as well as to determine the maximum efficiency conversion energy of DSSC using Mg-doped TiO2 and undoped TiO2 as photoanodes. The synthesis of TiO2 and Mg-TiO2 was carried out using the hydrothermal method with variations in the concentration of Mg dopant of 0, 0.5, 1, and 2% based on the molar ratio. The presenceof 2% of Mg in anatase TiO2 paste decreased the TiO2 band gap from 3.15 to 2.60 eV. Analysis results show that adding Mg dopant decreased the crystal size. Mg dopants on TiO2 could also form new energy levels, which reduced the band gap energy of TiO2. In addition, the increased concentration of Mg dopants also shifted the absorption capacity of TiO2 from the ultra-violet (UV) wavelengths region to the visible light area. The maximum energy conversion efficiency of the DSSCs with Mg-doped TiO2 photoanode of 0.5, 1, and 2% are 0.045; 0.070, and 0.172%, respectively, where these three efficiency values are higher than undoped TiO2 (0.017%). The results proved that the presence of Mg dopants on the TiO2 photoanode can increase the efficiency of DSSC.